Degenerative mitral regurgitation: assessment, physical examination, and imaging - Wunderlich, Nina C.; Beigel, Roy; Rader, Florian; Franke, Jennifer; Siegel, Robert J. (Current cardiology reports, 2019)
In this review, we provide a comprehensive approach to assess degenerative mitral regurgitation.
Gesehen am 17.01.2020